Effects of Low-Protein Diets Supplemented with Ketoacid on Expression of TGF-β and Its Receptors in Diabetic Rats. (15th December 2015) - Yang, Xiu; Yang, Ming; Cheng, Ming; Ma, Li-Bin; Xie, Xiang-Cheng; Han, Shuai; Zhang, Bo; Fei, Xiao; Wang, Ming; Mei, Chang-Lin
Abstract : TGF- β 1 has been recognized as a key mediator in DN. This study aimed to observe the effects of low-protein diets supplemented with ketoacid on mRNA and protein expression of TGF- β and T β RI and t T β RII receptors in the renal tissue of diabetic rats. A diabetes model was established in 72 male SD rats. They were then equally randomized to three groups: NPD group, LPD group, and LPD + KA group. Additional 24 male SD rats receiving normal protein diets were used as the control. Eight rats from each group were sacrificed at weeks 4, 8, and 12 after treatment, from which SCr, BUN, serum albumin, and 24 h urinary protein excretion were collected. The expressions of TGF- β 1, T β RI, and T β RII in LPD and LPD + KA groups were significantly lower than those in NPD group and lower in LPD + KA group than those in LPD group. Low-protein diets supplemented with ketoacid have been demonstrated to provide a protective effect on the renal function as represented by reduced SCr, BUN, and urinary protein excretion, probably through downregulating the gene expression of TGF- β 1 and its receptors in LPD + KA group.